Anmeldelser - Kullberg, Erling (Danish Yearbook of Musicology, 1999)
Review of: Lansing D. McLoskey: Twentieth Century Danish Music. An Annotated Bibliography and Research Directory (Music Reference Collection 65). Greenwood Press, Westport, Conneticut & London 1998.